2
$\begingroup$

Can anyone help me show that the following equations are equivalent?

$$x-\ln|1+e^x| = -\ln|e^{-x}+1|$$

I'm having a little trouble. It should be an easy solution, where I take one equation, start with it, and show that it can turn into the opposing one. I know it involves the properties of logs, but I am just stuck on it.

I got both the equations when solving for the anti-derivative of $1/(1+e^x)$, and am under the impression they are the same, but I do not understand how. I can show my work for this if it would help, just ask. Thank you.

Little help? Would appreciate any insight.

$\endgroup$
0
3
$\begingroup$

Hint: Try starting with $x=\ln(e^x)$ on the left side, to get $$\ln(e^x)-\ln(1+e^x) = -\ln(e^{-x}+1)$$ How can you use properties of logarithms to manipulate the left side further?

$\endgroup$
3
$\begingroup$

$$x-\ln|1+e^x|=-(-x+\ln|1+e^x|)$$ $$=-(\ln e^{-x}+\ln|1+e^x|)=-\ln(e^{-x}\cdot|1+e^x|) $$ $$=-\ln|e^{-x}+1|.$$ Above we used $a=\ln e^a$ and $\ln a+\ln b=\ln ab$.

$\endgroup$
3
$\begingroup$

Well, if those at the argument of the logarithms are absolute values, you can get rid of them since both $1+e^x$ and $1+e^{-x}$ are greater than $0$. On the other hand $$-\log(1+e^{-x})=\log\left(\frac{1}{1+e^{-x}}\right)=\log\left(\frac{e^x}{1+e^x}\right)=x-\log(1+e^x).$$

$\endgroup$
3
$\begingroup$

Note that $e^{-x}+1$ is always positive, as is $1+e^x$, so the absolute value bars are really irrelevant.

Then just do some algebra and use properties of the logarithm: $$\begin{align*} -\ln|e^{-x}+1| &= -\ln\left(\frac{1}{e^x} + 1\right)\\ &= -\ln\left(\frac{1+e^x}{e^x}\right)\\ &= \ln\left( \left(\frac{1+e^x}{e^x}\right)^{-1}\right)\\ &= \ln\left(\frac{e^x}{1+e^x}\right)\\ &= \ln(e^x) - \ln(1+e^x)\\ &= x - \ln(1+e^x)\\ &= x - \ln|1+e^x|. \end{align*}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.